Methodology for prediction of sub-surface residual stress in micro end milling of Ti-6Al-4V alloy. (February 2021) - Y, Rahul; K, Vipindas; Mathew, Jose
Highlights: Proposed a method to predict residual stress during micro end milling of Ti-6Al-4V Proposed model was validated with the experimental results Critical chip thickness in micro end milling was evaluated through FEM simulation Maximum residual stress was found at a depth of 2.5 μm from the machined surface Residual stress reduces to zero at a depth of 21 μm from the machined surface Abstract: To meet the growing demands of sophisticated component service life and miniaturization, the study of surface integrity such as residual stress after the machining becomes more essential. Compressive residual stress improves wear resistance of topological pairs and inhibits the fatigue crack propagation. To obtain a better understanding of state of residual stress at surface and sub-surface level, continuum-mechanics based Finite Element (FE) modeling is established. Dynamic explicit time incrementation scheme with coupled temperature displacement transient analysis is performed. Critical uncut chip thickness and consequences of tool edge radius, feed per tooth, and axial depth on cutting forces are investigated through FEM modeling. Besides the FEM modeling, the theoretical elastoplastic orthogonal cutting model with coupling of thermal and mechanical field variables is also demonstrated. In present research, Ti-6Al-4 V was chosen as the workpiece material because of its wide range of applications in biomedical, electronics, optics and aerospace industry due to their superior mechanical, chemical and high-temperature properties. X-ray diffraction (XRD) technique was used to measure the residual stress developed during micro-end milling process. Simulated results were validated with the experimental observations. To assess the residual stress at sub-surface level, electro polishing is done to remove the surface layer. It was found that both experimental and simulated results follow a similar trend and gave a good agreement between them.